The Influence of Socio-demographic Characteristics to Housing Satisfaction and Mobility - Agra Senopati Anand Prasetyo; Joko Adianto (International Journal of Built Environment and Scientific Research, 2022)
This study aims to understand the pivotal factors of housing satisfaction and mobility according to the demographic characteristics with its hindrances in Indonesia. Several studies prove the residents refuse to move despite experiencing housing dissatisfaction by adjusting the housing or adapting to the housing mostly because of the poor financial capacity or have realistic housing preferences to cope with the experienced housing dissatisfaction. This study employs a quantitative research method by collecting 534 respondents through an online questionnaire. According to the regression analysis, this study finds sex, age, monthly income, and marital status are the major demographic characteristics for driving housing satisfaction and mobility in the Indonesian context. In both sex categories, the increasing age tends to increase the monthly income and enter marriage, which enables the respondents to deliver housing mobility.